On the Grammatical Terms in Neo-Babylonian Grammatical Texts (IV) - Gamartum - Yoshikawa, Mamoru
in Japanese, English summary p. 20-21; the relation between t-separative and t-perfect in Akkadian may be assumed to exist between ba- šusḫurtum “non-ventive or separative” and ba- gamartum “perfective or terminative” in Sumerian; analysis of ba- verbal complex into middle and passive types.